Long-term agricultural fertilization alters arbuscular mycorrhizal fungal community composition and barley (Hordeum vulgare) mycorrhizal carbon and phosphorus exchange - Williams, Alwyn (The New phytologist, 2017)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.